Information Structure in Nigerian Pidgin English Print and Electronic Media Advertisements (2014)
Information structure provides a deeper understanding of how language is organised in Nigerian Pidgin English advertising discourse. Existing studies in Nigerian Pidgin English (NPE) advertisements have centred on describing its history, vocabulary items, standard orthography and aspects of grammar but there is a paucity of research on the information structure of pidgin texts. This study, therefore, investigated information structure in NPE advertisements in print and electronic media with a view to revealing the organisation of information for the establishment of their textual identities. M.A.K. Halliday’s model of Information and Thematic structures was applied in examining how theme and rheme combine to make up the thematic structure, the different ways in which the theme of a clause is realised and how it impinges on the meaning of an advertisement text. Fifteen spoken and fifteen written advertisement texts in NPE which were purposively sampled from print (newspaper/magazine/billboard) and electronic (radio/television/internet) advertisements formed the database. The samples were selected from a broad spectrum of products and services such as; beverages, household durables, pharmaceuticals, finance and communication. For the spoken texts, the transcription model adopted was the anglicised writing system used by Loreto Todd and the method for the analysis of data was discourse analytic. In NPE advertisements, information was organised in clauses which have constituents that are labelled Given and New. In the clauses, the Given element was first established by the advertiser before communicating the New information. This was done primarily to enhance comprehension of advert items. At the textual identity level, three varieties of theme in NPE advertisement texts, namely; Unmarked, Marked and Highly marked were used in the advertisements. While Marked and Unmarked themes were commonly used, the Highly marked theme rarely occurred. The information patterns varied: Topical+ Textual+ Interpersonal Themes and Rheme; Textual+ Textual Themes and Rheme; Topical+ Interpersonal Themes and Rheme. There were also substantial convergences and divergences in NPE print and electronic media advertisements. The notable areas of convergence were in the discourse structure of advertisement texts, the use of synthetic personalisation, mood systems, informal style, cohesive devices, referential indirectness, visual-verbal correspondence and tense patterns. Divergences occurred in graphology, space management, layout techniques, the use of different typefaces and letter sizes. Creativity was observed in well-designed and carefully-worded attractive headlines, picture-text convergence, picture-text divergence, the use of humour and figurative language. Information structure shows that the messages of pidgin texts connect as a unified discourse through the combination of Given and New elements while the textual identity reveals the constant theme-rheme patterns and their differential representations in print and electronic media advertisements. These features facilitate easy comprehension and recall of Nigerian Pidgin English advertising discourse.